A comparative study of critical phenomena and magnetocaloric properties of ferromagnetic ternary alloys. (January 2018) - Yüksel, Yusuf; Akinci, Ümit
Abstract: Magnetic and magnetocaloric properties, as well as the phase diagrams of a ferromagnetic ternary alloy system have been studied. A detailed comparison of two different methods, namely the effective field theory (EFT), and Monte Carlo (MC) simulations has been provided. Our numerical data show that the general qualitative picture presented by two methods are in a good agreement with each other. In terms of the magnetocaloric properties, our results yield that it is possible to design magnetic materials with a variety of working temperatures and magnetocaloric properties (such as large Δ S M and q values) by manipulating the magnetic phase transition via tuning the compositional factor (i.e. the mixing ratio of sublattice ions). The observed magnetocaloric effect has been found to be a direct one with Δ S M < 0 associated with a second order phase transition. Highlights: Ferromagnetic ternary alloy system has been investigated. Magnetic and magnetocaloric properties have been studied. Effective field theory and Monte Carlo simulations have been implemented. A direct magnetocaloric effect has been observed. Magnetocaloric properties are strongly dependent on the compositional factor p.